2011
DOI: 10.1002/ijc.25485
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cervical cancer associated with specific types of human papillomavirus: A case–control study in a UK population

Abstract: Mounting evidence supports incorporation of HPV testing into cervical screening; however, the optimal test format and target population have yet to be confirmed. Assessment of the potential benefits of type-specific testing requires estimation of the risk associated with infection with individual HPV types. However, the risk posed by individual HPV types may be population specific and influenced by cervical screening practice. The existing data on HPV type-specific risk is derived largely from unscreened popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
(88 reference statements)
1
22
0
1
Order By: Relevance
“…This risk difference was only found in younger women (<30 years), while in older women (⩾30 years) the risks between women positive for HPV16 and women positive for other hrHPV types were similar. This is in line with another study (Powell et al , 2011) that found that the mean age of women with HPV16-associated cancer was significantly lower than of nonHPV16-associated cancer. All CIN3+ in HPV16-positive women were identified within 5 years after detection of abnormal cytology, while lesions associated with other hrHPV types were also found in the 5 years hereafter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This risk difference was only found in younger women (<30 years), while in older women (⩾30 years) the risks between women positive for HPV16 and women positive for other hrHPV types were similar. This is in line with another study (Powell et al , 2011) that found that the mean age of women with HPV16-associated cancer was significantly lower than of nonHPV16-associated cancer. All CIN3+ in HPV16-positive women were identified within 5 years after detection of abnormal cytology, while lesions associated with other hrHPV types were also found in the 5 years hereafter.…”
Section: Discussionsupporting
confidence: 92%
“…All CIN3+ in HPV16-positive women were identified within 5 years after detection of abnormal cytology, while lesions associated with other hrHPV types were also found in the 5 years hereafter. This suggests that HPV16 has its main oncogenic effect within a shorter timeframe and at a younger age than other hrHPV types (Safaeian et al , 2009; Powell et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The methods of specimen selection, preparation and testing in each study were obtained from publications7 21 22 and study leads. A summary of methods of sample preparation and HPV testing is shown in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of HPV in cervical cancer and associated high-grade cervical lesions in the years immediately prior to immunisation have been conducted in England, Scotland, Wales7 21 22 and Northern Ireland (unpublished). However, each of these studies (and many from other countries) is limited in numbers to assess subgroups of particular interest, such as cancers in women aged <30 years.…”
Section: Introductionmentioning
confidence: 99%
“…HR HPV types 16/18 have the highest type-specific risk of cervical cancer development2 and predominate in 70% of cervical cancer cases worldwide 3…”
mentioning
confidence: 99%